2021
DOI: 10.1080/21639159.2021.1961599
|View full text |Cite
|
Sign up to set email alerts
|

Why Chinese travelers use WeChat to make hotel choice decisions: A uses and gratifications theory perspective

Abstract: WeChat, a Chinese multi-purpose messaging, social media, and mobile payment app, is an emerging social media platform that has been integrated into the daily lives of Chinese people, including travel. However, despite the growing proliferation of WeChat, surprisingly, little attention has been paid to the gratifications obtained by Chinese travelers when using WeChat in travel-related decision-making. Adopting (utilizing) the well ground concept of Uses and Gratifications theory (UGT), this exploratory work ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 98 publications
(177 reference statements)
1
16
0
Order By: Relevance
“…Nevertheless, the study results were not adequate in discussing what motivates viewers to watch travel vlogs. Gamage et al [18] apply a use and gratification (U&G) perspective to identify why and how tourists make travel decisions influenced by social satisfaction, process, and content.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the study results were not adequate in discussing what motivates viewers to watch travel vlogs. Gamage et al [18] apply a use and gratification (U&G) perspective to identify why and how tourists make travel decisions influenced by social satisfaction, process, and content.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It fails to differentiate between video categories. The data set used does not accurately reflect the video content Gamage et al [18] Variable: UGT theory (social satisfaction, process, and content), decision-making Result: The factors that influence consumer choice decisions include social satisfaction, processes, and content.…”
Section: Use and Gratification (Uandg) In The 1940s Psychologistmentioning
confidence: 99%
See 1 more Smart Citation
“…Hur et al [30] investigated the factors affecting social media continuance and information sharing with a lens of uses and gratifications theory in the travel and tourism. Gamage et al [31] also investigated gratifications obtained by Chinese tourists while utilizing WeChat system in making hotel selection decisions based on the uses and gratifications theory. The reported studies above mainly examined different information technology.…”
Section: Mobile Technology and Its Impact On Travel And Tourismmentioning
confidence: 99%
“…Prior literature uncovers three different classifications of trust levels relating to the message's source (Gamage et al, 2021;Varkaris and Neuhofer, 2017). They identified that the highest level of trust is associated with the content created by the personal circle of followers.…”
Section: H1: the Commercial Orientation Of The Social Media Influence...mentioning
confidence: 99%